Phytol Suppresses Osteoclast Differentiation and Oxidative Stress through Nrf2/HO-1 Regulation in RANKL-Induced RAW264.7 Cells - Eun-Nam Kim; Nguyen Minh Trang; Heesun Kang; Ki Hyun Kim; Gil-Saeng Jeong (Cells, 2022)
Osteoporosis is a systemic skeletal disorder where osteoclasts are prevalent among osteoblasts. Oxidative stress is one of the main causes of osteoporosis, and nuclear factor erythroid-2-related factor 2 (Nrf2) is the master regulator of antioxidant responses. Phytol, a diterpene isolated from Stevia rebaudiana leaves, has many biological effects, including antimicrobial, antioxidant, and anti-inflammatory effects. This study investigated the crosstalk between Nrf2 and osteoclast differentiation in the presence of phytol. Phytol inhibited osteoclast differentiation through TRAP-positive and F-actin formation. The expression of anti-nuclear factor of activated T cells-c1 (NFATc1) and c-Fos was suppressed by phytol, as shown using Western blot and RT-PCR analysis. Phytol inhibited oxidative stress by suppressing reactive oxidant species (ROS) accumulation while recovering antioxidant enzymes, including superoxide dismutase and catalase. Additionally, phytol ameliorated osteoclast-specific differentiation, function, and oxidative stress through Nrf2 regulation by siRNA transfection. In conclusion, these data demonstrate the inhibitory effect of phytol on osteoclast differentiation through Nrf2 regulation, suggesting its potential use in oxidative stress-related osteoporosis and bone diseases.